Taxonomic structure of bacterial communities in sourdoughs of spontaneous fermentation - V. K. Khlestkin; M. N. Lockachuk; O. A. Savkina; L. I. Kuznetsova; E. N. Pavlovskaya; O. I. Parakhina (Вавиловский журнал генетики и селекции)
The article is devoted to the study of the microbiome of spontaneously fermented sourdoughs. The aim of the work was to study the influence of the technological parameters of sourdough propagations on the taxonomic structure of the microbiome of spontaneously fermented sourdoughs. Two spontaneously fermented sourdoughs were studied: dense rye sourdough and liquid rye sourdough, both prepared using the same batch of peeled rye flour. To study the taxonomic structure of the sourdough microbiome in dynamics, the method of high-throughput sequencing of 16S rRNA gene fragments of microorganisms was used. It was shown that the technological parameters of sourdough (humidity, temperature) do not affect the taxonomic composition of the microbiome of dense rye or liquid rye sourdough at the phylum/class/genus level. It was found that during the first three days of propagations, bacteria from the phyla Proteobacteria and Firmicutes dominated in the microbial community. In the phylum Proteobacteria, microorganisms from the order Enterobacterales took a large share, which persisted for three days of backslopping. The phylum Firmicutes was represented by lactic acid bacteria of the genera Weissella, Lactobacillus, Leuconostoc, Pediococcus, Lactococcus. It was established by classical microbiological methods that after a day of fermentation, the number of lactic acid bacteria cells was significantly higher in liquid rye sourdough compared to dense one. However, with further propagation of sourdoughs, the number of cells was comparable, while significant changes occurred at the level of genera and species. It was shown that as the relative number of lactic acid bacteria of the genus Lactobacillus increased, a gradual displacement of the coccal forms of Lactococcus, Leuconostoc, Weissella, Pediococcus happened. With further propagation of sourdough after 10 days, the position of the dominant groups of bacteria was occupied by representatives of the phylum Firmicutes, lactic acid bacteria of the genus Lactobacillus. The influence of the mode and parameters of the sourdough on the species composition of lactobacilli, which demonstrated a low bacterial diversity, is shown. In the first three days of propagations, lactobacilli L. curvatus, L. brevis, and Lactiplantibacillus sp. dominated in both sourdoughs. After a month of backslopping, Fructilactobacillus sanfranciscensis and Companilactobacillus sp. dominated in dense rye sourdough, and L. pontis dominated in liquid rye sourdough.